“Saw you in the dark”: Exploring Rufus Wainwright’s emotional vulnerability in fan-captured live performance videos - Salerno, Stephanie (Performance Matters, 2019)
A Victorian-inspired, deplumed, black mourning gown; a video of a kohl-painted eye, staring, blinking, and weeping; and a baritone voice mingling with solo piano are the audio and visual touchstones of Rufus Wainwright’s 2010 live tour of All Days Are Nights: Songs for Lulu. Using performance analysis of fan-captured performances posted on YouTube, this article argues that digital viewership queers, or alters, the audience’s experience, thus empowering spectators to engage with the emotional vulnerability, grief, and genre-bending of Lulu. For a work like Lulu, performed as a song cycle and without official music videos or a professional live recording, fan videos fill a void, at once cutting a major expense of the artist/label while empowering the audience to capture and share what they find to be meaningful online. In this study, four fan-captured live Lulu performances reveal moments of elision, uncertainty, and the blurring of the artist and the artist’s persona within digital “third space.” Through this lens, persona and grief are read within digital viewings of Wainwright’s live performances while framing online spectatorship as a queer practice of meaning-making.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; culture populaire; deuil; identités LGBTQIA2+; masculinité; médias sociaux; new york; périodes historiques; queer; représentations médiatiques; ressource en ligne; régions géographiques; sofia; stéréotypes de genre; thématiques